Performance Analysis of Ultrathin Cu(In,Ga)Se2 Solar Cells with Backwall Superstrate Configuration Using AMPS-1D - Mouhoub, A.; Khaled, F.; Bouloufa, A. (Engineering, Technology & Applied Science Research, 2022)
This study used AMPS-1D to peform numerical simulations and model the behavior of back-wall superstrate solar cells based on Cu(In,Ga)Se2 (CIGS) thin films to investigate optimal conditions and obtain maximum efficiency. The effects of absorber thickness and density of interface defects were examined along with the work function of the transparent conductive oxide (WTCO) to investigate their influence on the output parameters. Measurements of device performance (J-V) and Quantum Efficiency (QE) showed that the performance of the cell improved as the thickness of the CIGS layer decreased because photons were absorbed near the junction. The device achieved an efficiency of 16.4% using an optimal thickness for the CIGS layer on the order of 0.3µm, defect densities in the range of 1013-1015cm-3, doping concentration of the n-TCO back contact on the order of 1019cm-3, and WTCO in the range of 4.5-5.2eV. These results show that the generated electron-hole pairs had a high probability of separation and demonstrate the potential of this device structure.